Studi Kelembagaan dalam Keberlanjutan Becak Tradisional di Kota Yogyakarta - Iscahyono, Achmad Fauzan; Kusumantoro, Iwan Pratoyo (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2023)
Sustainability of traditional pedicabs existence in Yogyakarta as one of the tourist attractions in supporting tourism has been able to survive for decades. It raises the allegation that the sustainability of traditional pedicabs existence as part of tourism in Yogyakarta tends to be due to the fulfillment of readiness in certain aspects that included in the concept of sustainable transportation, including social and institutional aspects. The aim of this research is to identify actor roles and networks in traditional pedicabs sustainability in Yogyakarta. This research uses content analysis and social network analysis (SNA) using UCINET and NetDraw software. Based on the analysis results, this research indicates that the relationship between all the actors involved in the network regarding the sustainability of the traditional pedicab is not going well. In addition, the Yogyakarta Bappeda is the actor who has the most significant role in the network regarding the sustainability of traditional pedicabs.